Differentiate Using The Product Rule And NOT The C

DrBob9

From: US
Posts: 34
Votes: 136
Differentiate using the product rule and NOT the chain rule y=x^2(sinx)(tanx)

 

Answer No.1

Anonymous

From: -
Posts: -
Votes: -
Y=x^2(sinx)(tanx) y' = d/dx(x^2(sinx)(tanx)) = x^2(sinx)d/dx((tanx)) + x^2d/dx((sinx)) (tanx) + d/dx(x^2) (sinx)(tanx) = x^2sinxsec^2x + x^2cosxtanx + 2xsinxtanx --> ans

Answer No.2

MathNewton52

From: US
Posts: 5
Votes: 20
Y=x^2(sinx)(tanx) y' = d/dx(x^2(sinx)(tanx)) = x^2(sinx)d/dx((tanx)) + x^2d/dx((sinx)) (tanx) + d/dx(x^2) (sinx)(tanx) = x^2sinxsec^2x + x^2cosxtanx + 2xsinxtanx = x^2sinxsec^2x + x^2sinx + 2xsinx tanx --> ans

Your Comment/Solution

Post As: Anonymous [Change]
Enter